Arabic Language Learning Evaluation: Analysis of Psychomotor-based Assessment Forms - Saajidah, Fauziyyah Hana; Mustofa, Triono Ali (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Evaluation is the most important part of the learning process because success and obstacles will only be known by the evaluation process. Of course different aspects of ability are different forms of evaluation used, besides that teacher creativity is also required in the implementation of evaluation. With regard to that, this study aims to analyze the form of psychomotor-based evaluation in Arabic language lessons and the supporting and inhibiting factors faced during the evaluation process. This research was conducted at SMP Muhammadiyah Al-Kaautsar PK Kartasura, using qualitative research with data collection techniques of observation, interviews and documentation studies. Research informants are Arabic language teachers and students. Data analysis uses the flow of data collection, data reduction, data presentation and conclusion drawing. The results of the study explain that there are four elements of language skills, namely, tests of listening skills or listening skills reading skills, speaking skills, and writing skills. Supporting factors are through additional observations of each student. The inhibiting factor is the lack of interest in learning Arabic because it is considered a burden, and the diverse backgrounds of students. The implications of this research can be the basis for improving Arabic language evaluation and can also be a best practice for other Arabic language teachers.